Cognitive Linguistics and Sociocultural Theory : Applications for Second and Foreign Language Teaching - Arnett, Carlee; Labarca, Angela; Masuda, Kyoko (Studies in Second and Foreign Language Education SSFLE, 2015)
By integrating cognitive linguistics and sociocultural theories, this groundbreaking book presents empirical studies on selected grammatical and semantic aspects that are challenging for second/foreign language learners. Through in-depth studies exploring eight different languages, this book offers insights generated through the synergy between cognitive linguistics and sociocultural theories that can be readily incorporated into teaching.